PEMBUATAN SABUN PADAT ANTISEPTIK EKSTRAK ETANOL KULIT JERUK LEMON (Citrus limon (L.) Burm. f.) - Eka Margaretha Sinaga; Barita Aritonang; Nova Florentina Ambarwati; Ahmad Hafizullah Ritonga (LPPM STIKes Indah Medan, 2021)
One of the herbal plants with antibacterial properties that it can use in solid antiseptic soap is lemon peel (Citrus limon (L.) Burm.F.). This study aims to determine the optimum composition of antiseptic solid soap preparations from the ethanolic extract of lemon peel based on the requirements set by SNI 06-4085-1996 and the antibacterial activity test. The antibacterial activity test was carried out by the good method. Examination of Simplicia characteristics was carried out by phytochemical screening test. The antiseptic solid soap preparation was performed by organoleptic test, pH test, homogeneity test, high foam test, and antibacterial activity test. The concentration variations of antiseptic solid soap preparations were F1(5%), F2(10%), and F3(15%). Based on the results of research that has been carried out, the results of phytochemical screening tests for lemon peels (Citrus limon (L.) Burm.F.) contain secondary metabolites, namely alkaloids, flavonoids, and triterpenoids that function as antibacterial. Antiseptic solid soap made from ethanolic extract of lemon peel has met the requirements set by SNI 06-4085-1996, namely a solid and homogeneous soap with a lemon scent with a pH of 8.71-10.52, high foam 4.7-4.9 cm, as well as free alkali in a safe condition against the skin. Based on the results of the antibacterial activity test of solid antiseptic soap, the ethanolic extract of lemon peel (Citrus limon (L.) Burm.F.) can inhibit the growth of Staphylococcus aureus bacteria. At a concentration of F1(5%) has a zone of moderate inhibition of 10.26 mm; at concentration F2(10%) has a strong inhibition zone of 11.78 mm; at the concentration of F3(15%) has a strong inhibition zone of 12.57 mm. Lemon peel extract can be formulated into a solid antiseptic soap with an optimum concentration of F3 (15%).